Estimation des teneurs en nitrates dans les eaux potables par l'utilisation de bandelettes réactives : un exercice d’éducation à l’environnement dans la vallée du Sourou au Burkina Faso - Francis Rosillon; Boubacar Savadogo; Aminata Kabore; Jean Noël Poda; Hortense Bado-Sama; Dayeri Dianou (VertigO)
Within the framework of the application of the contract of Sourou river in Burkina Faso, an estimation of the nitrates contents in waters was made by using a fast test by reagent strips. From 2008 to 2011, 29 drillings and wells and 9 points in surface waters located in the Sourou valley were the object of a comparative study between the test strips and the classic analysis in laboratory. The results were comparable in 90 % of the cases. We were able to verify simultaneously by both methods that the safe water WHO standard of 50 mg NO3/L was exceeded in the groundwater for 12 drillings and wells on 29 tested. Concentrations superior to 500 mg NO3/L were sometimes observed. The contaminations would be of multiple origins : animal and human defecation, latrines, waste water, and the use of dynamite for the digging having also been evoked. Beyond the use of a fast test to produce, at low cost, valid data estimating the nitrates contents in waters, this approach takes on an educational character following the example of the springs operations which had been organized in Belgium in the 90s. A transposition of this educational activity relative to the environment is suggested in Burkina Faso in association with schools.